The lamp of memory - Ruskin, John 1819-1900. (London Penguin Books, 2008)
States that ancient buildings must be conserved for their deep, mystical links with the past and that creative design is essential - not for financial gain, but to communicate eternal human truths. This title brings the works of the great thinkers, pioneers, radicals and visionaries whose ideas shook civilization and helped make us who we are.
Keywords: Architecture -- Conservation and restoration; Art appreciation; Art